Knowledge and utilization of partograph among health care professionals in public health institutions of Bale zone, Southeast Ethiopia. (August 2016) - Markos, D.; Bogale, D.
Abstract: Background: Partograph has been shown to be an efficacious tool for monitoring labor and identifying women in need of an obstetric intervention. Therefore, the aim of this study was to assess knowledge and utilization of partograph among health care professionals in public health institutions of Bale zone, Southeast Ethiopia. Study design: A facility-based cross-sectional study was conducted from February 1st to March 30, 2014. Methods: Single population proportion sample size determination formula was used to calculate the sample size and it was 401. Simple random sampling was employed to select both the health facilities as well as study subjects. Data were collected using pretested structured questionnaire. It was analyzed by SPSS for windows version 16.0. Descriptive, binary and multivariable logistic regression analyses were conducted. Statistically significant tests were declared at a level of significance of P value <0.05. Results: One hundred and forty (38.5%) and 224 (61.5%) study subjects have a poor and good level of knowledge about partograph, respectively. The magnitude of partograph utilization was 70.2%. Variables having statistically significant association with good level of knowledge about partograph were being midwives (AOR = 7.70, 95% CI = 2.38, 24.94), being nurses (AOR = 0.40, 95% CI = 0.19, 0.85) and being graduated from governmental higher institution (AOR = 2.04, 95% CI = 1.22, 3.42). Additionally, being female health professionals (AOR = 2.39, 95% CI = 1.17, 4.89), being hospital staff (AOR = 17.78, 95% CI = 2.32, 135.98) and receiving training about partograph (AOR = 2.94, 95% CI = 1.15, 7.54) have statistically significant association with partograph utilization. Conclusions: More than half of the respondents have a good level of knowledge about partograph. A significant number of study subjects reported use of partograph to monitor women in labour. It is recommended to provide periodic on-job training on partograph to all obstetric caregivers especially for nurses and public health officers to improve their knowledge. Highlights: Among the total respondents, 140 (38.5%) and 224 (61.5%) of them have poor and good level of knowledge about partograph, respectively. The magnitude of partograph utilization is about 70.2%. Professional qualification and institution where the respondents are graduated from were independent predictors of respondents' knowledge of partograph. The independent predictors of partograph utilization were sex of the respondents, institution where they were working and receiving training on partograph.